LGBTQI+ Healthcare (in)Equalities in Portugal: What Can We Learn from Asexuality? - Alcaire, Rita (Healthcare (Basel), 2021)
The main purpose of this article is to analyse how healthcare providers in Portugal perceive asexuality. To do so, the author makes use of qualitative data from both the CILIA LGBTQI+ Lives project and The Asexual Revolution doctoral research on asexuality in Portugal, namely, a focus group conducted with healthcare providers, drawing from their assessment of interview excerpts with people identifying as asexual. The data were explored according to thematic analysis and revealed three major tendencies: (1) old tropes at the doctor’s office; (2) narratives of willingness to learn about the subject; and (3) constructive and encouraging views of asexuality. From this analysis, valuable lessons can be drawn concerning the respect for gender and sexual diversity. The author argues that both formal and informal learning play an important role in building cultural competence among healthcare providers. This could be achieved both by introducing sexual and gender diversity in curricula in HE and through media exposure on these subjects. Overall, it will lead to building knowledge and empathy about marginalised groups, and will help fight inequalities of LGBTQI+ people in healthcare. As such, LGTBQI+ activism that puts the topics of asexuality and LGBTQI+ in the media agenda, is a powerful strategy. Hence, because healthcare providers show willingness to learn, the media becomes a source for learning about asexual and LGTBQI+ experiences, which they can incorporate in their medical practice.